Cómo afecta el consumo de alcohol de los adultos a la distribución intra-hogar del gasto y al bienestar de los ni\~nos? Evidencia para Argentina a partir de un modelo colectivo de demanda; How does adult alcohol consumption affect intra-household expenditure distribution and children's well-being? Evidence for Argentina from a collective demand model - Miriam Berges; Lucía Echeverría; Martina Menon; Federico Perali (Estudios de Economía, 2025)
– Alcohol consumption by one member of the household generates negative externalities in the family budget, affecting the distribution of expenditure and the well-being of the other members. Significant reductions in the resources allocated to children associated with high alcohol consumption by adults can have negative consequences for their long-term development. This paper analyses whether alcohol consumption by adults is associated with the distribution of expenditure within households, affecting the well-being of children. We estimate a collective demand model for Argentina using data from the 2017/2018 National Household Expenditure Survey (ENGH). The estimates allow us to identify the proportion of total expenditure allocated to adults and children, focusing on families with different levels of alcohol consumption. This work presents the first evidence for Latin America on the relationship between alcohol consumption and the allocation of expenditure within the household. Results indicate that intense alcohol consumption is linked to a lower child well-being, as it is associated with a redistribution of resources within the home in favor of adults.
Keywords: D12; D13; 330; Collective model; demand system; sharing rule; alcohol consumption; intra-husehold expenditure allocation